2020
DOI: 10.3390/s20247264
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Fabrication of an MOEMS Gyroscope Based on a WGM Resonator

Abstract: In this paper, the characterization of a whispering gallery mode (WGM) resonator applied in a novel micro-opto-electro-mechanical system (MOEMS) gyroscope was investigated. The WGM optical transmission coupling model was analyzed and compared by adjusting key parameters, such as the cavity radius, the waveguide width, and the gap between them for silicon and silicon nitride materials in simulations, which will greatly affect the quality factor (Q) of the WGM resonator. Furthermore, the structural parameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Moreover, based on the MOEMS techniques, in 2020, D. Xia et al [114][115][116] reported an electrostatically driven MEMS gyroscope with the nested ring structure and detected by the whispering gallery mode (WGM) mode, as shown in Fig. 8(d).…”
Section: Nested Ring Micro-gyroscopementioning
confidence: 99%
“…Moreover, based on the MOEMS techniques, in 2020, D. Xia et al [114][115][116] reported an electrostatically driven MEMS gyroscope with the nested ring structure and detected by the whispering gallery mode (WGM) mode, as shown in Fig. 8(d).…”
Section: Nested Ring Micro-gyroscopementioning
confidence: 99%
“…While MEMS sensors effectively enable linear vibration monitoring, conventional MEMS gyroscopes have seen limited application in angular vibration measurement due to typical resolutions in the order of microradians [13][14][15][16]. However, recent advances integrating micro-opto-electromechanical systems (MOEMS) have prompted new gyroscopic designs capable of pushing these boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…While MEMS sensors effectively enable linear vibration monitoring, conventional MEMS gyroscopes have seen limited application in angular vibration measurement due to typical resolutions on the order of microradians [13][14][15][16]. However, recent advances integrating micro-optoelectromechanical systems (MOEMS) have prompted new gyroscopic designs capable of pushing these boundaries.…”
Section: Introductionmentioning
confidence: 99%